Mona Lisa (enigmatic) Smile: Women and Societies in Conflict - de Paula, Luciane [UNESP]; Sant’ana, Carolina Gomes [UNESP] (FapUNIFESP (SciELO), 2022)
This article analyses how the woman is semiotized in the movie Mona Lisa Smile (2003), aiming to think about how the conflict between tradition and revolution reflects and refracts social values of what it means to be a woman. Centered on the protagonists, this study focuses on traditional and subversive social voices in conflict. The reflection on the internal-external valuation movement that constitutes subjects-women and societies in the great time of culture justifies its relevance. It analyzes the film in its verbivocovisual unity. The Bakhtinian theoretical foundation supports the analysis in its dialectical-dialogical-historical materialist methodological movement, using mainly the concepts of dialogue, ideology, and social voices. To analyze issues related to feminism, studies from Beauvoir, Saffioti, Davis, Studart, hooks, and Ribeiro will be used. The results reveal how the social pressure on women affects them and impacts society. Mona Lisa Smile semiotizes historical and cultural movements in resurgence in the contemporaneity and reflecting on this is urgent.
O sorriso (enigma) de Mona Lisa: mulheres e sociedades em embate
Keywords: Bakhtinian studies; dialogy; ideology; social voice; women